‘We give our blood’: from tiger victim to conservation hero (Bardiya, south-west Nepal) - Nolwen Vouiller (European Bulletin of Himalayan Research)
On 6 January 2004, at the end of the Maoist rebellion, Bhadai Tharu was attacked by a tiger in the Khata Corridor Forest, south-west Nepal, on the border with India; he had been elected chairperson of this forest six months earlier. Due to this ‘sudden encounter’ (jamkā-bhet), in which he lost an eye, his life changed completely, apparently for the better. Regarded as a ‘conservation hero’ by various media, foreigners and locals, and receiving visits from legendary actors such as Leonardo DiCaprio and Rajesh Hamal, Bhadai Tharu has rapidly become someone whom anyone interested in narratives of animal attacks around Bardiya National Park has to meet. With his lively stories and songs that leave a strong impression on those who listen to him, Bhadai embodies the resilience and the unconditional ‘love’ that we have towards wildlife. Based on the interview I conducted with him in November 2021, on what has been published about him in several media sources and on what some informants have to say about his story, I analyse a process of heroisation and the choice of ‘giving blood’ to conservation endeavours. This narrative echoes many other encounters that have occurred in Bardiya since 2019 and might be the case of many more to come.